The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/hr.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of automated oscillometric measurement of the ankle-brachial index for lower arterial occlusive disease by comparison with computed tomography angiography

Abstract: The ankle-brachial index (ABI) determined by the oscillometric method has been shown to reliably detect peripheral arterial disease (PAD), with highly correlations with the Doppler method. However, most of these studies were shown in cohorts with a small number of PAD patients, and no imaging studies have been performed. The purpose of this study is to evaluate the diagnostic accuracy and optimal threshold of oscillometric ABI for detecting PAD using computed tomography angiography (CTA) as a gold standard in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
3
25
0
1
Order By: Relevance
“…In ours, only the Doppler ABI calculation based in standard formulas or not and diabetes achieved statistical significance in dOR to explain heterogeneity, in such a way that those studies with a standard Doppler calculation and those with a low prevalence of diabetes exhibited higher values of dOR. These findings emphasise the lack of accuracy of the oscillometric ABI in diabetic patients, as has been previously reported in studies using both ultrasound and angiographic confirmation . As meta‐regression analyses suggested, this lack of accuracy especially occurs at the expense of sensitivity, which emphasises the use of cut‐off values greater than 0.9 for diabetic patients (values between 1.0 and 1.1 have been suggested) .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In ours, only the Doppler ABI calculation based in standard formulas or not and diabetes achieved statistical significance in dOR to explain heterogeneity, in such a way that those studies with a standard Doppler calculation and those with a low prevalence of diabetes exhibited higher values of dOR. These findings emphasise the lack of accuracy of the oscillometric ABI in diabetic patients, as has been previously reported in studies using both ultrasound and angiographic confirmation . As meta‐regression analyses suggested, this lack of accuracy especially occurs at the expense of sensitivity, which emphasises the use of cut‐off values greater than 0.9 for diabetic patients (values between 1.0 and 1.1 have been suggested) .…”
Section: Discussionsupporting
confidence: 57%
“…previously reported in studies using both ultrasound and angiographic confirmation. 48,49 As meta-regression analyses suggested, this lack of accuracy especially occurs at the expense of sensitivity, which emphasises the use of cut-off values greater than 0.9 for diabetic patients (values between 1.0 and 1.1 have been suggested). 48 The physiological explanation seems to be calcification, which turns the artery wall rigid and poorly compressible, making ABI less reliable, especially for the oscillometric method.…”
Section: Discussionmentioning
confidence: 99%
“…The AngSc is negatively correlated with maximum treadmill walking distance 12 and ankle-brachial pressure index (ABPI), 13 which is a functional measure of the severity of PAD. 14 Furthermore, AngSc is an independent risk factor for major amputation in diabetic subjects with PAD. 15 Previous studies have shown that PAD is associated with metabolic dysbalances 16 and AS.…”
Section: Introductionmentioning
confidence: 99%
“…However, several publications have advised to use ABI ≤1 for oscillometric techniques. 14 17 In that case, MESI device reached 85% of sensitivity and 96% specificity to detect PAD in at least one leg.…”
Section: Resultsmentioning
confidence: 84%
“… 18 However, several authors have reported that using a cutoff value closer to 1 was better to diagnose PAD surely because of the systematic small overestimation of oscillometric method. 14 17 When using 1 as a cutoff value, the MESI ABPI MD device sensitivity was 85% and 96% for specificity showing excellent detection of PAD. In our study, PAD diagnosis was solely based on Doppler ABI results.…”
Section: Discussionmentioning
confidence: 99%